Maternal Amino Acid Mixtures Supplementation during Late Gestation and Lactation Improved Growth Performance of Piglets through Improving Colostrum Composition and Antioxidant Capacity - Xiongkun Yuan; Xiangyu Zhang; Yujun Wu; Dongsheng Che; Hao Ye; Yu Pi; Shiyu Tao; Junjun Wang; Dandan Han (MDPI AG, 2022)
During late gestation and lactation, oxidative stress in sows can affect their health and reproductive performance. Supplemental amino acid contributes to the antioxidant capacity of pigs. This study was conducted to evaluate the effects of different combinations of Gln, Leu and γ-GABA (amino acid mixtures, AAMs) during late gestation and lactation on the performance of the sows and their offspring. Fifty large white × landrace sows were randomly assigned to 5 groups (n = 10), including a control group and four AAMs groups (AAMs1, Gln + Leu; AAMs2 (Gln + GABA; AAMs3, Leu + GABA; AAMs4, Gln + Leu + GABA). AAMs supplementation improved the antioxidant capacity of sows, including significantly enhanced total antioxidant capacity in AAMs2, 3 and 4 groups and reduced malonaldehyde concentration in AAMs1, 3 and 4 groups. Additionally, all AAMs significantly increased lactoprotein, total solid and IgA levels of colostrum in sows during lactation. Average body weight of piglets on day 21 after birth in all AAMs groups were significantly increased. Furthermore, the significantly increased total antioxidant capacity was observed in the piglets of every AAMs group. In conclusion, supplementing AAMs during late gestation and lactation improved the antioxidant capacity of sows and colostrum composition, thereby enhancing antioxidant status and the growth performance of piglets. This study provides the possibility of maternal amino acid mixtures to improve the productivity of the swine industry.